2023
DOI: 10.1002/adfm.202301816
|View full text |Cite
|
Sign up to set email alerts
|

All‐Organic Smart Textile Sensor for Deep‐Learning‐Assisted Multimodal Sensing

Abstract: Smart textile for sensor is identified as a superior platform with greatly improved convenience and comfort for wearable bioelectronics. However, most reported textile-based sensors cannot fully demonstrate the inherent advantages of textiles, such as comfortability, breathability, biocompatibility, and environmental friendliness, mainly due to the intrinsic limitation of non-textile or inorganic components. Here, an all-textile, all-organic, washable, and breathable sensor with discriminable pressure, proximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Differently, for noncontact proximity sensing, the presence of an object above the capacitor sensor ( C 1 ), such as a hand (Figure a), can act as another electrode and form a new capacitor ( C 2 ) with air as the dielectric layer. The presence of C 2 weakens the electric field in the sensor, leading to a decrease in C 1 . As shown in Figure b, finite element analysis was further applied to show the change of the electric field (represented by red lines) around the sensor when an object approaches (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differently, for noncontact proximity sensing, the presence of an object above the capacitor sensor ( C 1 ), such as a hand (Figure a), can act as another electrode and form a new capacitor ( C 2 ) with air as the dielectric layer. The presence of C 2 weakens the electric field in the sensor, leading to a decrease in C 1 . As shown in Figure b, finite element analysis was further applied to show the change of the electric field (represented by red lines) around the sensor when an object approaches (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of C 2 weakens the electric field in the sensor, leading to a decrease in C 1 . 30 As shown in Figure 5b, finite element analysis was further applied to show the change of the electric field (represented by red lines) around the sensor when an object approaches (Figure 5b). It can be seen that as the distance between the object and the sensor is reduced from 20 to 10 cm, the electric field of the sensor is weakened.…”
Section: Resultsmentioning
confidence: 99%
“…Utilizations of touchless electronics in human healthcare applications could be attributed to their excellent sensing abilities of humidity, temperature, and airflows (Figure F). Infrared thermometers are extensively adopted to monitor body temperature to provide real-time information about human health status. Airflow perception could help humans to respond to noncontact stimuli in uncertain environments (for example, dark, noisy, etc.)…”
Section: Intelligent Deploymentsmentioning
confidence: 99%
“…Copyright 2017 American Chemical Society. Reproduced with permission from ref . Copyright 2023 Wiley-VCH.…”
Section: Intelligent Deploymentsmentioning
confidence: 99%
“…22,23 Enhanced research and development efforts have resulted in the emergence of fibers or textiles that possess sensing, memory, communication, and other advanced capabilities. 24–27 Materials possessing properties relevant to personal health management, such as moisture absorption and sweat-wicking abilities, thermochromism, and antibacterial functionalities, have garnered significant attention due to their potential in enhancing the practicality of fibers and textiles while improving bodily comfort and elevating daily life quality. 28–32 Recently, Wang et al reported a moisture-wicking passive cooling hierarchical metafabric based on nanofiber membranes that combines selective optical cooling and wick-evaporation cooling to achieve efficient temperature and moisture management.…”
Section: Introductionmentioning
confidence: 99%